The Well-Being of Children. Philosophical and Social Scientific Approaches - Schweiger, Gottfried (De Gruyter, 2015)
This volume explores the questions related to the theory, practice, and policy of the well-being and well-becoming of children. It does so in a truly interdisciplinary way with a focus on the social sciences and philosophy, giving therefore justice to the growing insight that studying and promoting the well-being of children has a strong ethical component. It is dependent on the questions of good life, its conditions and cannot be separated from the concept of social justice and moral entitlements of children and their families. In this book, philosophers and social scientists, in close dialogue, shed light on some of the most challenging matters involved.